The Relationship between Cerebral Small Vessel Disease, Hippocampal Volume and Cognitive Functioning in Patients with COPD: An MRI Study - Cleutjens, Fiona A. H. M.; Ponds, Rudolf W. H. M.; Spruit, Martijn A.; Burgmans, Saartje; Jacobs, Heidi I. L.; Gronenschild, Ed H. B. M.; Staals, Julie; Franssen, Frits M. E.; Dijkstra, Jeanette B.; Vanfleteren, Lowie E. G. W.; Hofman, Paul A.; Wouters, Emiel F. M.; et al. (Frontiers in Aging Neuroscience, 2017)
The neural correlates of cognitive impairment in chronic obstructive pulmonary disease (COPD) are not yet understood. Structural brain abnormalities could possibly be associated with the presence of cognitive impairment through cigarette smoke, inflammation, vascular disease, or hypoxemia in these patients. This study aimed to investigate whether macrostructural brain Magnetic Resonance Imaging (MRI) features of cerebral small vessel disease (SVD) and hippocampal volume (HCV) are related to cognitive performance in patients with COPD. A subgroup of cognitively high and low-performing COPD patients of the COgnitive-PD study, underwent a brain 3T MRI. SVD as a marker of vascular damage was assessed using qualitative visual rating scales. HCV as a marker of neurodegeneration was assessed using the learning embedding for atlas propagation (LEAP) method. Features of SVD and HCV were compared between cognitively high and low-performing individuals using Mann Whitney U tests and independent samples t-tests, respectively. No group differences were reported between 25 high-performing (mean age 60.3 (SD 9.7) years; 40.0% men; FEV1 50.1% predicted) and 30 low-performing patients with COPD (mean age 60.6 (SD 6.8) years; 53.3% men; FEV1 55.6% predicted) regarding demographics, clinical characteristics, comorbidities, and the presence of the SVD features and HCV. To conclude, the current study does not provide evidence for a relationship between cerebral SVD and HCV and cognitive functioning in patients with COPD. Additional studies will be needed to determine other possible mechanisms of cognitive impairment in patients with COPD, including microstructural brain changes and inflammatory,- hormonal,- metabolic,- and (epi)genetic factors.